A necrópole da Idade do Ferro de Vale da Palha (Calhariz, Sesimbra) - Arruda, Ana Margarida (2015)
In January of 1958 four rectangular graves with inhumations were identified through rural works carried out in Vale da Palha (Sesimbra). Eduardo da Cunha Serrão came in the field and was informed that all the skeletons had a vase with them. These data were published in 1974, and the necropolis was dated in the late roman times, IV century AD. This chronology was based in a graffito incised in one of the vases that was assimilated to a M of the Latin alphabet. Only two of the three vases recovered are now available to study. They are hemispheric bowls and they could be included in Iron Age Grey Polish Pottery category. In morphologic terms, they correspond to the most frequently form of this pottery, present in almost every orientalised sites of the Iberian Peninsula. Both graffiti could be also related with a Mediterranean tradition. The presence of an Iron Age necropolis in the area isn’t a surprise, because in the Estuary of Sado’s river the remains of communities with a Mediterranean origin are well known.